Fast and Accurate Computation of Wireless Power Transfer System Optimal Design Using Particle Swarm Optimization Method - Sim, Boogyo; Shin, Taein; Park, Hyunwook; Son, Keeyoung; Kim, Keunwoo; Lho, Daehwan; Kim, Seongguk; Yoon, Jiwon; Kim, Hyunwoo; Lee, Junghyun; Kim, Juneyoung; Kim, Joungho (IEEE transactions on electromagnetic compatibility, 2023)
In this article, for the first time, the wireless power transfer (WPT) system achieved optimal design by fast and accurate computation using a particle swarm optimization (PSO). The high power transfer efficiency (PTE) is determined by the dimension of the coil and the other parameters such as the operating frequency and ferrite structures. Therefore, the complex and high-dimensional design parameters of the WPT system have to be determined with optimal coil design. By the conventional FEM electromagnetic (EM) simulation such as Ansys Maxwell, it is impossible to optimize the coil design since it needs a huge amount of running time about several tens of minutes for only one simulation and the EM simulation does not consider the frequency-dependent results. One of the optimization methods, PSO algorithm is a powerful solution to resolve the large computation time and frequency-dependent results using the fast and accurate random data set generator. The results demonstrated that the optimal coil design by the PSO revealed the optimal PTE of the WPT system. Therefore, we can say that the PSO can carry out fast and accurate computation for optimization of the more real cases of WPT system considering the effect by the ferrite.